2021
DOI: 10.1093/nar/gkab677
|View full text |Cite
|
Sign up to set email alerts
|

NMPylation and de-NMPylation of SARS-CoV-2 nsp9 by the NiRAN domain

Abstract: The catalytic subunit of SARS-CoV-2 RNA-dependent RNA polymerase (RdRp) contains two active sites that catalyze nucleotidyl-monophosphate transfer (NMPylation). Mechanistic studies and drug discovery have focused on RNA synthesis by the highly conserved RdRp. The second active site, which resides in a Nidovirus RdRp-Associated Nucleotidyl transferase (NiRAN) domain, is poorly characterized, but both catalytic reactions are essential for viral replication. One study showed that NiRAN transfers NMP to the first … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
70
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(78 citation statements)
references
References 63 publications
7
70
1
Order By: Relevance
“…The function of nsp9 nucleotidylation is less clear, with current studies proposing its involvement in either protein-primed RNA synthesis or the regulation of m 7 G cap synthesis. Nsp9 nucleotidylation is also not dependent on the nsp12 RdRp domain, possibly because RNA binding is not required for this reaction ( 18 , 20 ). Interestingly, all of these proposed activities utilise the same nsp12 D218 amino acid residue as the GTase reaction, raising the possibility that the NiRAN domain uses a single active site to carry out several diverse functions in coronavirus RNA synthesis (Figure 3G ) ( 19 , 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…The function of nsp9 nucleotidylation is less clear, with current studies proposing its involvement in either protein-primed RNA synthesis or the regulation of m 7 G cap synthesis. Nsp9 nucleotidylation is also not dependent on the nsp12 RdRp domain, possibly because RNA binding is not required for this reaction ( 18 , 20 ). Interestingly, all of these proposed activities utilise the same nsp12 D218 amino acid residue as the GTase reaction, raising the possibility that the NiRAN domain uses a single active site to carry out several diverse functions in coronavirus RNA synthesis (Figure 3G ) ( 19 , 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…The fact that nsps are formed by autocatalytic cleavage of polyproteins would suggest that the identities of their terminal residues are perhaps physiologically important. Indeed, we and others showed that the very first residue of nsp9 is NMPylated by NiRAN; 8 , 22 consequently, the native N-terminus is absolutely essential for nsp9 modification and viral replication in turn. 8 We also showed that AS2 can transfer RDV-monophosphate to nsp9; 22 an nsp9 thus mis-modified may be unable to support the viral life cycle.…”
Section: The Errors Of Their Waysmentioning
confidence: 87%
“…Indeed, we and others showed that the very first residue of nsp9 is NMPylated by NiRAN; 8 , 22 consequently, the native N-terminus is absolutely essential for nsp9 modification and viral replication in turn. 8 We also showed that AS2 can transfer RDV-monophosphate to nsp9; 22 an nsp9 thus mis-modified may be unable to support the viral life cycle. While the exact role of nsp9 is yet unknown, its RNA-binding activity is thought to be critical.…”
Section: The Errors Of Their Waysmentioning
confidence: 87%
See 2 more Smart Citations